(untitled) (Bioagro, 2026)
Rubus fruits are prized in fresh and processed products due to their high nutritional value, aroma, and colour. This study aimed to evaluate the variation in the physicochemical properties of blackberries (Rubus floribundus Kunth) during ripening in Norte de Santander, Colombia. Fruits were harvested according to their phenological stage (Ff) during ripening (Ff83, Ff85 and Ff87) according to the BBCH scale. Physical and chemical parameters were determined based on Ff and the measurement time (Tm). These were determined according to Ff and measurement time (Tm). A 3x6 factorial design was employed, incorporating three levels of Ff and six Tm (weeks). The results showed significant main effects (p≤0.001) and interactions (p≤0.001) between phenological phases (Ff) and measurement times (Tm). Significant increases (p≤0.001) were observed during ripening according to Ff in equatorial diameter (DE), mass (M), pH and total soluble solids (SST), with the highest values recorded for Ff87 (12,77 mm; 4,03 g; 2,78; 8,81 °Brix, respectively). There was also a significant, high, positive linear correlation (r=0.808; p≤0.001) between DE and M. The maturity index (IM) and SST showed significant differences (p≤0.05) according to Ff, with the highest values recorded as the fruit ripened; while the total titratable acidity (ATT) recorded a significant decrease (p≤0.05) according to Ff, with the lowest value recorded for Ff87 (1.24 % malic ác.). These findings provide valuable information to help determine the optimal harvest time and establish quality standards for producers and the processing industry alike.